Immune checkpoint inhibitor induced large vessel vasculitis. Issue 5 (18th May 2020) - Henderson, Daisy; Eslamian, Gelareh; Poon, Daniel; Crabb, Simon; Jones, Robert; Sankey, Peter; Kularatne, Bihani; Linch, Mark; Josephs, Debra
Abstract : This is a case report of a 67-year-old patient with castration resistant metastatic prostate cancer who developed an immune-mediated large vessel vasculitis following treatment with ipilimumab (anti-CTLA-4) and nivolumab (anti-PD-1).